REVIEW: ANALYTICAL NARRATIVE IN-DEPTH UNDERSTANDING OF FORMULATION METHODS AND TRANSFERSOME CHARACTERIZATION FOR THERAPEUTIC APPLICATIONS - Setiyawan, Sukamto Jodi; Astuti, Ika Yuni; Hariyanti , Hariyanti (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
Transdermal drug delivery systems offer a non-invasive method for drug penetration through the skin but face significant challenges, especially in the stratum corneum layer, which inhibits drug penetration. Transfersome, an elastic vesicle developed from one of the nanocarriers, liposomes, has proven effective in increasing transdermal drug penetration. To examine manufacturing methods, evaluate potential safety aspects, and apply transfersomes to increase transdermal penetration of active ingredients. The results of the article search showed that transfersomes have advantages in terms of adsorption efficiency, elasticity, and the ability to carry drugs with various vesicle sizes. Several transfersome manufacturing methods have been developed, such as thin-film hydration, reverse evaporation, high-level homogenization, sonication, and ethanol injection, each with advantages and disadvantages. The thin-film hydration method is often used in research because it results in high adsorption efficiency, superior penetration ability, and good compatibility. Transfersomes have proven to be effective elastic vesicle delivery systems with phospholipids and surfactants. In transdermal applications, transfersome successfully improve the penetration and therapeutic effectiveness of antioxidant, anticancer, corticosteroid, and anti-inflammatory drugs, in the context of increasing drug penetration and therapeutic effectiveness. Transfersomes are promising drug delivery systems for transdermal applications, offering increased penetration, bioavailability, and therapeutic effectiveness. Appropriate formulation methods and in-depth characterization are needed to optimize the therapeutic potential of transfersomes for various medical applications. Keywords: Transfersomes, transdermal delivery, lipid vesicles, entrapment efficiency, vesicle deformability, transfersome manufacturing method.